2019
DOI: 10.1016/j.celrep.2019.01.104
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Induces NK-Cell-Mediated Type-II IFN Response that Regulates Humoral Immunity in an IL-6-Dependent Manner

Abstract: The role of natural killer (NK) cells in the immune response against vaccines is not fully understood. Here, we examine the function of infiltrated NK cells in the initiation of the inflammatory response triggered by inactivated influenza virus vaccine in the draining lymph node (LN). We observed that, following vaccination, NK cells are recruited to the interfollicular and medullary areas of the LN and become activated by type I interferons (IFNs) produced by LN macrophages. The activation of NK cells leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…IL-6, as an important mediator of the acute phase response or as an anti-inflammatory cytokine, is secreted by macrophages to stimulate the immune response during infection. IL-6 induces intracellular signaling cascades that give rise to inflammatory cytokine production in inflammatory cells, such as neutrophils (van der Poll et al, 1997;Gao et al, 2018;Farsakoglu et al, 2019). In our study, PGPS induced neutrophil infiltration (Figure 1).…”
Section: Discussionsupporting
confidence: 50%
“…IL-6, as an important mediator of the acute phase response or as an anti-inflammatory cytokine, is secreted by macrophages to stimulate the immune response during infection. IL-6 induces intracellular signaling cascades that give rise to inflammatory cytokine production in inflammatory cells, such as neutrophils (van der Poll et al, 1997;Gao et al, 2018;Farsakoglu et al, 2019). In our study, PGPS induced neutrophil infiltration (Figure 1).…”
Section: Discussionsupporting
confidence: 50%
“…It has previously been shown that this proinflammatory cytokine is produced in vitro and in vivo in response to MVA in whole blood, PBMCs, primary human monocytes, and macrophages (27,28). IL-6 plays an important role in B-cell maturation, is closely associated with antibody production during infections and vaccination, and positively regulates the anti-influenza B-cell responses (24,(29)(30)(31)(32)(33). IL-6 is also considered a cytokine adjuvant that enhances immune response to vaccines (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In humoral immunity, neutralizing antibodies can prevent the adsorption of the virus, via opsonization, and primarily interact with extracellular free viruses (Murasko et al, 2002). Activated Th1 cells release various cytokines (i.e., IFN-γ and TNF), activate macrophages and NK cells to induce further inflammatory reactions, and promote the proliferation and differentiation of cytotoxic T lymphocytes (CTLs), which play an important role in antiviral infection (Julkunen et al, 2001; Farsakoglu et al, 2019). However, studies have shown that while an inflammatory response helps to clear pathogens, excessive inflammatory reactions do not only protect the host organism but also cause the additional damage.…”
Section: Discussionmentioning
confidence: 99%